Antioxidants as potential pharmacotherapeutic agents in managing male infertility - Braich, Jarnail S.; Singh, Surinder; Kamal, Hemant (International Journal of Research in Medical Sciences, 2022)
Globally, infertility affects 8-12% of couples of reproductive age. Infertility among males accounts for 20%-30% of global infertility cases. Most male infertility cases are idiopathic, with oxidative stress as the underlying mechanism. Reactive oxygen species (ROS), in high concentrations, can outweigh the endogenous antioxidant capacity and interfere with male reproductive processes. Excess ROS levels adversely affect male fertility, but their physiological concentration is vital to mediate the normal sperm functions. The current review aims to evaluate the potential role of antioxidants in the pharmacotherapy of infertility among males.